Investigating the Reaction of Coal Bottom Ash (CBA) as Partial Cement Replacement in Mortar - Geragop, Rosnika Henda; Mokhatar, Shahrul Niza (Recent Trends in Civil Engineering and Built Environment, 2023)
Malaysia generates approximately 8.5 million tonnes of coal ash as waste, which includes bottom ash and fly ash. Increasing amounts of coal bottom ash (CBA) from coal power plants becomes raising concerns as a huge amount of waste is currently landfilled. The wide production of Portland cement has a great environmental concern in terms of carbon dioxide (CO2) emissions. This study investigates the effect of varying ratios of alkali-activated coal bottom ash (CBA) as a partial replacement for cement mortar. CBA mixtures have been activated with the calcium chloride CaCl2 solution. Mix proportion used for this study was 1:3: 0.5. Four sample were used in this study. CBA were used as a partial cement replacement (CBA/OPC) at varying ratios of 0%, 20%, 40%, and 60% mixed with 0%, 2%, 4% and 6% alkali activator content which is Calcium Chloride (CaCl2) as a core binder. The effects of these substitutions on the workability were investigated using the Flow Table Test according to ASTM D 792. The result found that the increase CBA, the increase of flow in mortar. The exterior mould for determining mortar hydration temperature was a 300 mm x 300 mm x 450 mm cube of plywood. It was filled with 76 mm thick polystyrene, which served as an insulator. To fill the mortar mix, a polyvinyl chloride (PVC) pipe with a diameter of 150 mm and a height of 300 mm is used. In the centre of each box a thermocouple (Type K) was inserted and connected to a data logger system. Temperature rises due to heat of hydration were recorded in all mixes for 72 hours. The use of a mortar containing a mixture of CBA and CaCl2 was found to be effective in reducing the heat of hydration produced during the curing period and hardening paste. Physical properties CBA were analyse using Particle size analyser (PSA) according to ASTM C 1467 standard. Identical result found from the (PSA) has confirmed that CBA can be utilized as supplementary cementitious material when the specific gravity for both CBA and OPC is shown 2.67, respectively. Other than that, the particles diameter of CBA D10, D30, and D60 are more finess than OPC.